Pendampingan Bimbingan Dan Konseling Bagi Guru Sebagai Edukasi Pengentasan Masalah Peserta Didik Dalam Proses pembelajaran - Nurul Azmi Saragih; Aminda Tri Handayani; Ika Sandra Dewi; Macharani Adi Putri Siregar (LPPI UMN AL WASHLIYAH, 2025)
Guidance and Counseling is part of education for a teacher to be able shape the character of students so they can have a personality that can overcome problems in their learning process individually. Nowadays, not only teachers who have a guidance and counseling major are allowed to carry out process of eliminating student problems, but subject teachers and homeroom teachers are required to be able carry out the general guidance process in the classroom, therefore it is important for a teacher to be able understand guidance and counseling in general as a form of providing motivation or alleviating problems for students when they experience difficulties while studying either in class, school or at home. The Madrasah where community service is carried out is one of places where it is necessary provide assistance regarding guidance and counseling for teachers as education to overcome problems for students in their learning process. The methods used start from process of managing permits, socialization, preparation and implementation/activities, presentation results and final evaluation. The results of community service carried out at this Madrasah showed an increase in understanding of guidance and counseling for teachers starting from pretest before material was given to after material was given.